2013
DOI: 10.1177/1367493513489780
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of physicians’ engagement of children with asthma in treatment-related discussions

Abstract: Our objectives were to examine whether providers engage children with asthma in treatment-related discussions at the level children prefer (engagement concordance) and to determine whether engagement concordance is related to child, caregiver, and provider characteristics. Children with asthma (n = 296) aged 8–16 years were recruited at five pediatric practices in North Carolina. Using audiotaped medical visit transcripts, we documented the number of treatment-related questions the providers asked the children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…42 One group which used audio-tape recently reported that both children (8-16 years old) and parents were asked for their input into asthma treatment plans during only 7.8% and 9%, respectively, of visits, 43 and that one third of providers did not ask these children any treatment-related questions. 44 Our finding that disagreement between the physician, whether pediatrician or pediatric pulmonologist, and the child is significantly greater when the parents have a higher level of education or when the physician believes there is good adherence to the inhaled steroids treatment is of interest. It suggests that physicians may be biased by impression.…”
Section: Discussionmentioning
confidence: 82%
“…42 One group which used audio-tape recently reported that both children (8-16 years old) and parents were asked for their input into asthma treatment plans during only 7.8% and 9%, respectively, of visits, 43 and that one third of providers did not ask these children any treatment-related questions. 44 Our finding that disagreement between the physician, whether pediatrician or pediatric pulmonologist, and the child is significantly greater when the parents have a higher level of education or when the physician believes there is good adherence to the inhaled steroids treatment is of interest. It suggests that physicians may be biased by impression.…”
Section: Discussionmentioning
confidence: 82%
“…Adolescents believed these features could enhance asthma-related communication with school nurses, friends, and providers, which is an important domain of asthma self-management [12]. Because providers often ask adolescents how often they use their control and rescue medications and experience with symptoms, data collected via apps that can be displayed in an easy-to-read graphical format could potentially enhance adolescent-provider communication during office visits [45]. These data could also potentially be transmitted directly to the child's electronic health record [46].…”
Section: Discussionmentioning
confidence: 99%
“…Other analyses with these data have shown that even though children and caregivers express problems with their asthma medications, they are very unlikely to ask questions about these problems during the visit [42]. Moreover, additional analyses have revealed that even though over 95% of children in the study wanted to be involved in treatment-related discussions, one-third of providers did not ask children any treatment-related questions [43]. Taken together, these findings suggest that providers may need assistance with creating an environment where families can engage more in asthma-related discussions.…”
Section: Discussionmentioning
confidence: 98%